Assesment of land use in Klang for the year 2010 and 2020 / Muhammad Syawal Addin Hazerinaf Hata and Muhammad Mirza Razin Sarizam - Hazerinaf Hata, Muhammad Syawal Addin; Sarizam, Muhammad Mirza Razin (Universiti Teknologi MARA (UiTM), 2024)
Over the past ten years, Klang, a historic city and major economic centre in Selangor, has seen substantial industrial and urban expansion. The study's mapping and comparing of land use trends shows how agricultural and underdeveloped regions are changing into industrial and residential zones. With the use of advanced GIS programs like ArcGIS Pro and ERDAS Imagine, this study examines how land usage has changed in Klang, Malaysia, between 2010 and 2020.The results highlight how the city's environment is impacted by population increase, infrastructural development, and economic activity. To minimize negative effects and guarantee that Klang's future growth is both ecologically and financially feasible, recommendations place an extreme value on its importance of environmentally friendly planning and the environment techniques.